The PBB Story: Michigan Farmer's Investigative Reporting Scoops the Nation - Richard Lehnert (Journal of Applied Communications, 1978)
I don't know what image you have of Michigan, but it has undoubtedly been affected by the polybrominated biphenyl (PBB) contamination.